Knowledge Management towards Sustainable Development as Stated in the Philosophy of Sufficiency Economy: A Case Study in Kong Thanu subdistrict, Mueang Lop Buri District, Lop Buri Province - Jujia, Sawitree; Somwang, Chirawan; Sukim, Sonthaya (Journal of Roi Et Rajabhat University, 2023)
The aims of this research were to 1) gather, categorize, and establish a sustainable social capital database in accordance with the sufficiency economy philosophy, 2) analyze the factors that influence the management of sustainable development patterns in production and consumption, as outlined in the sufficiency economy philosophy, 3) create a model for managing the patterns of sustainable development in production and consumption, as outlined in the sufficiency economy philosophy, and 4) disseminate knowledge about sustainable development in production and consumption, as outlined in the sufficiency economy philosophy. This study employed a qualitative research methodology. The investigation was conducted in the village numbered 1 to 14, located in Kong Thanu subdistrict, Mueang Lop Buri district, Lop Buri province. The research samples included of the senior management team of Kong Thanu subdistrict administrative organization, as well as representatives of community leaders and villagers. The research methodology employed in this study involved the utilization of in-depth interviews and focus group discussions as the primary data collection instruments. The data were examined using content analysis. The research findings demonstrate that the development of social capital is sustained in accordance with the principles of the sufficiency economy philosophy in both production and consumption. This is evident in the outcomes of the projects "Ban Nee Mee Rak Plook Pak Kin Aeng" (cultivating vegetables for personal consumption) and "Tang Nee Mee Phol Poo Kon Rak Kan" (Share the Love, Share the Veggies), which have contributed to the villagers’ food security, good health, access to organic vegetables, and overall well-being in their pursuit of sufficiency living. Additionally, another exemplary approach can be observed in the Kong Thanu concept for community garbage management, which employs the 3Rs principle. The villagers exhibited a high level of discipline and cooperation in order to effectively sort household rubbish. The recyclable rubbish was transported to be sold at the recycling center. Consequently, every village was immaculate. The locals maintained high standards of cleanliness and lived in a healthy environment. Consequently, Kong Thanu subdistrict emerged as the epitome of a model community and a center for learning. The factors that influenced the management of sustainable development patterns, as outlined in the sufficiency economic concept, can be observed in the elements of "leadership team, Boworn teamwork, and positive change". Their successful accomplishment of their work objectives may be attributed to the implementation of His Majesty King Bhumibol Adulyadej’s work development principles, which include understanding, obtaining insight and access, and actively participating in development.